2021
DOI: 10.1097/md.0000000000027134
|View full text |Cite
|
Sign up to set email alerts
|

Management of chronic myeloid leukemia presenting with isolated thrombocytosis and complex Philadelphia chromosome

Abstract: Rationale: Chronic myelogenous leukemia (CML) with thrombocytosis and complex chromosomal translocation is extremely rare in clinical setting. Here, we reported the clinical and pathological characteristics of CML patients, which were characterized by thrombocytosis and complex Philadelphia chromosome translocation. Moreover, we also introduced our therapeutic schedule for this patient as well as review relative literature. Patient concerns: A 24-year-old female present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Unlike regular ABL1, this protein features an enzymatic domain with heightened and constant tyrosine kinase activity due to its fusion with BCR. This uncontrolled tyrosine kinase activity has been associated with the underlying mechanisms of CML [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike regular ABL1, this protein features an enzymatic domain with heightened and constant tyrosine kinase activity due to its fusion with BCR. This uncontrolled tyrosine kinase activity has been associated with the underlying mechanisms of CML [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there is an excessive presence of granulocytes and their immature precursors, occasionally accompanied by blast cells. The defining genetic abnormality is the translocation of t(9;22)(q34;q11.2), leading to the formation of the BCR/ABL1 fusion gene, commonly referred to as the Philadelphia chromosome [ 1 ]. CML constitutes 20% of all adult leukemia cases.…”
Section: Introductionmentioning
confidence: 99%
“…Only 12.5% of patients had WBC < 50 000 elts/mm 3 , 33.3% had WBC > 200 000 elts/mm 3 15 patients presented with pronounced thrombocytosis and moderate leucocytosis and who were referred with a suspected diagnosis of essential thrombocythemia [14].…”
Section: This Study Confirms That An Earlier Age Of Diagnosis Exists Inmentioning
confidence: 98%
“… 3 Although more than 90% of CML patients are associated with typical t(9; 22)(q34; q11), but about 5–8% of newly diagnosed CML patients are associated with complex variant Ph (vPh) chromosome, involving one or more chromosomes in addition to 9 and 22. 4 The mechanism of vPh chromosome translocations generation and its effect on prognosis is unclear, but may further classify CML in specific subsets requiring different therapeutic approaches. However, some previous studies have suggested that CML patients with vPh chromosome may have a worse prognosis than patients with typical translocations, including 3 cases with CML with three-way complex vPh t(6;9;22) chromosome translocations.…”
Section: Introductionmentioning
confidence: 99%